Survival prognostic factors and molecular aspects in extremity soft tissue sarcoma - Bogdan Serban; Eugen Radu; Adrian Cursaru; Bogdan Stefan Cretu; Sergiu Andrei Iordache; Madalina Cîrnu; Cosmin Florentin Niculae; Cătălin Florin Cîrstoiu (Journal of Mind and Medical Sciences)
Soft tissue sarcomas are defined as relatively rare, wide-ranging mesenchymal tumors that present several forms of aggressive behavior. In order to improve the therapeutic result and thus the patient's prognosis, reliable diagnostic and evaluation tools are needed, capable of establishing the evolutive pattern of each patient. Materials and Methods. An analytical observational study was conducted in the period 2016-2023 in the Orthopedics Department of the Bucharest University Emergency Hospital, on patients diagnosed with soft tissue sarcoma. Data such as sex, age, site, size, depth, histotype, grade and margin status, vessel or bone involvement, adenopathies, adjuvant therapy, clinical findings, etc., were analyzed. Diagnosis included immunohistochemistry after macroscopic pathological findings were carefully reviewed by a dedicated pathologist. A molecular study was performed to increase the accuracy of diagnosis, prognosis and clinical management of selected sarcomas. Results. In adult soft tissue sarcomas, histotype has been reported to be a significant predictor of overall survival. In terms of survival rate, vascular invasion appears to be a significant pathological factor for progression in extremity STS. Even though the local control of the disease has improved, the development of systemic metastases seems to be largely influenced by the biological characteristics of the tumor. Conclusions. Significant prognostic factors for the likelihood of a lower survival and death rate are tumor size, tumor depth, histology type, and vascular invasion. The results of the study support and complement the literature data, thus improving the understanding of the prognosis of soft tissue sarcomas.